Examining the role of affective states in relation to exercise intentions and participation in extra-curricular exercise classes at university: A repeated measurement observational study - Finne, Emily; Nigg, Carina; Weyland, Susanne; Sauzet, Odile; Wienke, Benjamin; Jekauc, Darko (Frontiers in Psychology, 2022)
Background: Previous research has shown evidence of the role of affective states for physical activity behavior. However, there is a lack of research investigating the interplay between affective states, intentions, and exercise behavior, especially with respect to maintaining regular exercise over time. The study aimed to investigate whether post-exercise affective states and changes during exercise i) are related to exercise intentions, ii) moderate the relationship between intention and subsequent exercise behavior, and iii) directly predict future exercise. Methods: Participants from weekly voluntary sports and gym classes at two universities were recruited. For 13 weeks, 268 individuals’ (M_age= 24.5 years, SD=5.6, 90% students, 67.4% female) class attendance was documented on a weekly basis. Before and immediately after the training, participants self-reported affective states, including affective valence (Feeling Scale) and perceived arousal (Felt Arousal Scale). Participants also reported their intention to re-attend the class the following week. Mixed-effect linear models and Cox proportional hazard models were used to examine the relationships between affective states and change in affective states, re-attendance intentions, and class re-attention. Results: Affective valence at the end of training was significantly positively associated with the intention to re-attend the class on both the within-person level (β = .880, p < .001) as well as the between-person level (β = .831, p < .001). Higher increases of valence reduced this effect. For class re-attendance, significant effects of affective states were only found on the within-person level. A one-point increase on the valence scale increased the hazard ratio to re-attend by 8.4% (p < .05), but this effect was no longer meaningful after adjusting for intention. No moderation of the relationship between intention and subsequent class re-attendance was found. Conclusions: The results suggest that positive affective states immediately after exercise do not facilitate the translation of intentions into subsequent exercise behavior (i.e. they do not close the intention-behavior gap). Rather, affective valence was found to be an important predictor of exercise intentions, but seemed indirectly related to behavior via intentions. Practitioners should plan exercise programs in a way that allows for positive affective states especially at the end of a training.